EFEKTIFITAS KINERJA SOLAR CELL PADA PLTS DENGAN SUMBER 50WP - Catra Indra Cahyadi (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2020)
The need for electricity for both industry, offices, and the general public and individuals is greatly increasing. However, this increase in electricity demand was not accompanied by an increase in electricity supply. Based on these problems, solar energy is chosen as an alternative energy to produce electrical energy. The tools used here are solar cells, because they can directly convert solar radiation into electrical energy (photovoltaic process). So that solar energy can be used at night, during the day the electrical energy produced is stored first to a battery which is controlled by the regulator. The regulator output is directly connected to the inverter from DC to AC currents. The results of solar module testing (photovoltaic) show that the results of research with a 50WP solar cell can use a maximum load of 325 Watts. This is because the solar cell when following the direction of the sun's movement will always position the solar cell to remain facing the sun so that it will still be able to capture the sun's rays to the maximum.